Influence of transformation leadership style on employee engagement among Generation Y - Mansor, Zuraina; Mun, Cheong Pooi; Bambang Suito, Nurul Farhana; Wan Mohamed Tarmizi, Wan Aisyah Nasuha (World Academic Publishing, 2017)
The aim of this research is to determine the influence of transformation leadership style on employee engagement among Generation Y. The growing of Generation Y employees in Malaysia has raised concerns about how to engage and motivate this cohort. Transformation Leadership style is one of the key factors to increase employee engagement levels in the organization. This study has proven to be important for the researchers and the organization to properly understand the concept of employee engagement, transformation leadership style and their relationship. The samples in this study included 221 respondents of Generation Y who are currently working in Selangor and Klang Valley area in Malaysia. The data were collected using questionnaires and analyzed by using Statistical Package for Social Science (SPSS). The results show that there is a significant relationship between the dimension of intellectual stimulation, inspiration motivation and individual consideration on employee engagement. In contrast, the results have revealed that there is no significant relationship between idealized influences of a leader on employee engagement among Generation Y.